Non-catalytic participation of the Pin1 peptidyl-prolyl isomerase domain in target binding - Innes, Brendan T.; Bailey, Melanie L.; Brandl, Christopher J.; Shilton, Brian H.; Litchfield, David W. (Frontiers in Physiology, 2013)
Pin1 is a phosphorylation-dependent peptidyl-prolyl isomerase that has the potential to add an additional level of regulation within protein kinase mediated signaling pathways. Furthermore, there is a mounting body of evidence implicating Pin1 in the emergence of pathological phenotypes in neurodegeneration and cancer through the isomerization of a wide variety of substrates at peptidyl-prolyl bonds where the residue preceding proline is a phosphorylated serine or threonine residue (ie. pS/T-P motifs). A key step in this regulatory process is the interaction of Pin-1 with its substrates. This is a complex process since Pin1 is composed of two domains, the catalytic PPIase domain, and a type IV WW domain, both of which recognize pS/T-P motifs. The observation that the WW domain exhibits considerably higher binding affinity for pS/T-P motifs has led to predictions that the two domains may have distinct roles in mediating the actions of Pin1 on its substrates. To evaluate the participation of its individual domains in target binding, we performed GST pulldowns to monitor interactions between various forms of Pin1 and mitotic phospho-proteins that revealed two classes of Pin-1 interacting proteins, differing in their requirement for residues within the PPIase domain. From these observations, we consider models for Pin1-substrate interactions and the potential functions of the different classes of Pin1 interacting proteins. We also compare sequences that are recognized by Pin1 within its individual interaction partners to investigate the underlying basis for its different types of interactions.